The effect of using a multimedia program on developing reading skill among kindergarten children A study on a sample of kindergarten children (the third category) in the Jableh city - Hajjah, Rana (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The research aims to reveal the effect of using a multimedia program in developing the reading skill of kindergarten children, semi-experimental approach has been adopted, by designing two groups, one of which is control and the other is experimental. The researcher designed a multimedia program by using the computer and presented it to the experimental group children, while it was not presented to the control group.. A linguistic scale for reading skill was used by the researcher to achieve the goals of the research, after verifying the validity of the scale and its consistency, it was applied to the experimental sample of (10) boys and girls and the control (12) boys and girls. The researcher used non-parametric tests (which are tests that depend on the free distribution of the sample) to study the differences between the averages of the grade levels of children on the linguistic scale of reading skill, and the results of the research showed that there are differences between the average grade levels of children of the experimental group and the average grade of children’s grades of the control group for post-application on The same scale, as it was found that there were no differences between the average levels of children’s grades for males and females in the experimental group, and the research showed that there were no differences between the average levels of children’s grades for the experimental group on the post and postponed applications on the scale. يهدف البحث إلى الكشف عن أثر استخدام برنامج وسائط متعددة في تنمية مهارة القراءة لدى أطفال الروضة، ولتحقيق ذلك تم اعتماد المنهج الشبه التجريبي، وذلك بتصميم مجموعتين إحداها ضابطة والأخرى تجريبية. وقد قامت الباحثة بتصميم برنامج وسائط متعددة باستخدام الحاسوب وعرضه على أطفال المجموعة التجريبية في حين لم يتم عرضه على المجموعة الضابطة. لتحقيق أهداف الدراسة تم استخدام مقياس لغوي خاص بمهارة القراءة من تصميم الباحثة لتحقيق أهداف البحث، بعد التحقق من صدق المقياس وثباته تم تطبيقه على عينة البحث التجريبية البالغ عددها (10) طفلاً وطفلة والضابطة (12 طفلاً وطفلة). استخدمت الباحثة الاختبارات اللامعلمي (هي الاختبارات التي تعتمد على التوزيع الحر للعينة) لدراسة الفروق بين متوسطات رتب درجات الأطفال على المقياس اللغوي الخاص بمهارة القراءة، وقد أظهرت نتائج البحث وجود فروق بين متوسط رتب درجات أطفال المجموعة التجريبية ومتوسط رتب درجات أطفال المجموعة الضابطة للتطبيق البعدي على المقياس ذاته، كما تبيّن عدم وجود فروق بين متوسطي رتب درجات الأطفال ذكور وإناث المجموعة التجريبية، وبيّن البحث عدم وجود فروق بين متوسط رتب درجات أطفال المجموعة التجريبية على التطبيقين البعدي والمؤجل على المقياس.